Mutations in the gene for the E1β subunit: a novel cause of pyruvate dehydrogenase deficiency - Brown, R; Head, R; Boubriak, I; Leonard, J; Thomas, N; Brown, G (Springer, 2004)
We describe two unrelated patients with pyruvate dehydrogenase (PDH) deficiency attributable to mutations in the gene encoding the EIβ subunit of the complex. This is a previously unrecognised form of PDH deficiency, which most commonly results from mutations in the X-linked gene for the E1β subunit. Both patients had reduced immunoreactive E1β protein and both had missense mutations in the E1β gene. Activity of the PDH complex was restored in cultured fibroblasts from both patients by transfection and expression of the normal E1β coding sequence.